McDonaldization of society - Ritzer, George (SAGE, 2013)
George Ritzer's McDonaldization of Society, now celebrating its 20th anniversary, continues to stand as one of the pillars of modern day sociological thought. By linking theory to 21st century culture, this book resonates with students in a way that few other books do, opening their eyes to many current issues, especially in consumption and globalization. As in previous editions, the book has been updated and it offers new discussions of, among others, In-N-Out- Burger and Pret A Manger as possible antitheses of McDonaldization. The biggest change, however, is that the book has been radically streamlined to offer an even clearer articulation of the now-famous McDonaldization thesis.